El ocaso del latifundio Greene: ilegalidad, política internacional y agrarismo en la frontera Sonora-Arizona, 1954-1958 - Grijalva Dávila, Miguel Ángel (El Colegio de México, A.C., 2018)
This article describes the vicissitudes surrounding the expropriation of the Greene estate in 1958, explaining how the farmworkers’ movement in northwestern Mexico and U.S. foreign policy aligned for the expropriation of this property, the largest in Sonora, which had been under the control of U.S. companies. It also illustrates how the Institutional Revolutionary Party (PRI) regime was able to reduce social pressures and avoid unrest in the countryside in the mid-20th Century. This article is the product of a doctoral thesis that utilized information found in contemporary press accounts, Mexico’s National Archives, the U.S. National Archives and Records Administration (NARA), as well as texts found online.